HUBUNGAN KETEPATAN PENILAIAN TRIASE DENGAN TINGKAT KEBERHASIALAN PENANGANAN PASIEN CIDERA KEPALA DI IGD RSU HKBP BALIGE KABUPATEN TOBA SAMOSIR - Mila Gustia; Melva Manurung (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2018)
One indicator success of emergency medical response is the speed of providing sufficient help to emergency patients either on a regular daily basis or during a disaster and the successful handling of head injuries to save lives or prevent disability since the incident, on the way to hospital help.Triage is a special process of sorting out patients based on the severity of injury or illness to determine the type of emergency care. Triage is based on ABCDE, the severity of the injury, the number of patients coming, the available health facilities and the likelihood of life of the patient. Triage nurses use ABC nursing such as airway, breathing and circulation, as well as skin color, humidity, temperature, pulse, respiration, level of awareness and visual inspection for deep wounds, gross deformities and bruises to prioritize care provided to patients in the emergency room. Principles of initial handling include primary and secondary surveys. In primary management prioritized on ABCDE (Airway, with cervical spine control, Breathing and circulation with bleeding control, disability and exposure) followed by resuscitation. Triage is a way of selecting patients based on therapeutic needs and available resources. Triage assessment is the process of assessing a patient based on the severity of a head injury or determining the type of emergency treatment. Design of the research used correlation research method with samples 17 people. Sampling of this research using probability sampling with Proportionate stratified random sampling, research conducted in January 2017. The result of the research found triage of nurse to head injured patient seen that majority of nurses succeeded in doing triage assessment as much as 14 people (82.36%). The correlation of the accuracy of the evaluation of the nurses Triage with the success rate of the patient's handling of Head Injury at IGD HKBP Balige Hospital with the result of Pearson Product Moment test with r = 0.327 which means there is a significant correlation between the accuracy of the nurse Triage assessment with the success rate of the patient's head injury at IGD of HKBP Balige. Therefore it is expected to the Hospital in order to maintain the results of fast response time and precisely, and further improve its services, especially in the emergency department.Key words : Triage assessment, handling, patient, head injuries